Phenomena and Social Problems of Marriage Youth in Kampar District Riau Province - Zikri Darussamin; Ahmad Fauzi; Ahmad Zikri; Darmawan Tia Indrajaya; Rahman Rahman (International Journal of Islamic Thought and Humanities, 2023)
The existence of the Marriage Law No. 1 of 1974 and the provisions of the National Family Planning Coordinating Board (BKKBN) regarding the minimum age limit for marriage have yet to reduce the number of young marriages in Indonesia successfully. This study aimed to examine the factors causing young marriages to occur in Kampar Regency, Riau Province. This study uses quantitative principles. Data was collected using a questionnaire filled in by 225 respondents who married at a young age (men married less than 19 years and women less than 16 years). Factors causing marriage at a young age are divided into two, namely internal factors and external factors. There are nine items to measure internal factors and ten to measure external factors that cause marriage at a young age. Data were analyzed using the frequency test, descriptive test and crosstabulation test. The results showed that the most potent internal factor causing marriage at a young age was because they wanted to maintain their innocence from the dangers of promiscuity (mean=3.83). In contrast, the most dominant external factor was their parents' lack of religious education (mean=3 .30) and the destructive influence of watching TV/movies (mean=3.28). This study has proven that respondents were still happy with their marriage. This means that marriage at a young age will only sometimes end in conflict and divorce.